Microscopic Evidence for Strong Interaction between Pd and Graphene Oxide that Results in Metal‐Decoration‐Induced Reduction of Graphene Oxide. Issue 15 (24th January 2017) - Jeon, Jong‐Myeong; Kim, Taemin Ludvic; Shim, Young‐Seok; Choi, You Rim; Choi, Seokhoon; Lee, Seonyong; Kwon, Ki Chang; Hong, Seong‐Hyeon; Kim, Young‐Woon; Kim, Soo Young; Kim, Miyoung; Jang, Ho Won
Abstract : Graphene oxide (GO) is reduced spontaneously when palladium nanoparticles are decorated on the surface. The oxygen functional groups at the GO surface near the nanoparticles are absorbed to the palladium to produce a palladium oxide interlayer. Palladium therefore grows on the GO with preferred orientations, resulting in unique microstructural and electrical properties.